Saúde mental na atenção primária: uma cartografia - Araújo, Roseane Rocha (2019)
The restructuring of the mental health care model, after the Psychiatric Reform movements, has deinstitutionalization as the care proposal and main strategy for Psychosocial Rehabilitation and the social reintegration of users in an integrated way with the cultural environment and the community in which they are inserted. This study has a qualitative nature, which aimed to map the care for people in distress or with mental disorder provided in the Family Health Strategy in the municipality of Sobral. The theoretical references used in this process are those that support the discussions for the organization of Psychosocial Care expressed by the Psychiatric Reform and the principles and experiences of deinstitutionalization, the care brought by Emerson Merhy, an author who provides subsidies for the proposed theme, as well as rehabilitation psychosocial relevance to Saraceno. Cartography as a method made it possible to monitor the movements and paths of mental health care, the forces that drive the actions that drive the articulation of the Health Network. The primary data were obtained through semi-structured interviews with professionals in the health network. de Sobral - Ce, semi-structured interviews with managers and technicians with higher education who perform mental health care and through visits for participant observation and in mental health actions offered at Family Health Centers during the period from September to October 2019. The results pointed to the need to strengthen the Psychosocial Care Network, due to the political obstacles experienced in the current Brazilian situation. The study subjects revealed a feeling of helplessness, anguish as well as unpreparedness of Primary Care in the management of mental health cases, emphasized obstacles to the effectiveness of the bond, the effectiveness of the articulation of the health network in daily life. The discussion on mental health and its effectiveness in Primary Care still remains an aspiration, needs to be strengthened and effective in its Mental Health practices.